Analisis Pengembangan Produk Ekspor Woven Earth Craft - Ais Mariya Ulva; R. Yuniardi Rusdianto (International Forum of Researchers and Lecturers, 2024)
Exports are goods and services produced in one country and sold to buyers in another country. The biggest contributing factor to Gross Domestic Product is exports.